Effects of CrN coating of cylinders on engine performance - Hazar, Hanbey; Oner, Cengiz; Nursoy, Mustafa (Sila Science, 2009)
In an experimental study performed on a single cylinder four stroke diesel engine, the cylinder was coated with CrN by PVD and its surface behaviors were investigated. Performance improvements of the engine with CrN coated cylinder and with uncoated cast iron cylinder were compared. Exhaust emission values, exhaust gas temperatures, specific fuel consumptions (SFC), and torque and power outputs were taken into account as performance indicators. CrN coated engines were performed better at almost all categories. The test results evidenced that, No. 2D fuel can be used in ceramic coated diesel engines successfully.
Keywords: Diesel engines; Engine performance; Exhaust emissions; CrN coating; Cylinder